Development of Android-Based Mathematics Learning Media Using Google Sites to Enhance Learning Motivation - Maharani, Erizindya; Wijayanti, Rica (JED (Jurnal Etika Demokrasi), 2025)
Students often face problems in learning mathematics, such as boredom and lack of motivation due to monotonous learning media. This study aims to develop android-based learning media with google sites. This study uses the Research and Development (RD) method with the ASSURE model. Validation of the learning media was carried out by two material expert validators and two media expert validators to ensure the quality and feasibility of the media developed. The results of the validation test showed that the developed learning media was very valid, with a percentage of material experts of 96% and media experts of 98%. The results of the practicality test showed that the media was classified as very practical, with an average teacher response of 92% and a student response of 88%. The effectiveness test conducted on 28 students of class VIII G showed that the developed learning media was effective, with a classical level of student learning completion reaching 87%. This study has succeeded in developing android-based mathematics learning media using google sites that can improve student motivation and learning outcomes. The implications of this study indicate that the application of technology in mathematics learning, especially through the use of google sites, is an effective solution to overcome the problem of boredom in learning.